2009
DOI: 10.1002/piq.20044
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond competencies: An exploratory study in defining exemplary workplace learning and performance practitioners

Abstract: G ilbert (1978), in his book Human Competence, discussed the notion of performance improvement potential (PIP) and noted a big difference between the productivity of individual performers. A trend in recent years was to focus attention on developing and hiring best-in-class performers, who are called exemplars, rather than training or hiring merely qualified performers (Dubois & Rothwell, 2004). The research presented here offers insight into the identification of these behaviors and characteristics that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Empathy clearly aligns with T&D competencies involving interpersonal relationships, particularly leadership, service delivery, and teamwork. Empathy was also a common feature of behaviors demonstrated by exemplary performers in T&D work (Smith, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Empathy clearly aligns with T&D competencies involving interpersonal relationships, particularly leadership, service delivery, and teamwork. Empathy was also a common feature of behaviors demonstrated by exemplary performers in T&D work (Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…Empathy shares content with T&D competencies demanding high proficiency and central to many T&D tasks as well as pervasive in interactions with a variety of T&D counterparts (Arnesen et al, ). One study suggested that empathy may be central to exemplary T&D performance (Smith, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to skill training, the P-T approach is aimed to an extent at creating practitioner skills representative of exemplary performers in areas such as entrepreneurial and visionary planning identified by Smith (2009).…”
mentioning
confidence: 99%